Walk two moons - Creech, Sharon (New York : HarperTrophy, 2004)
Thirteen-year-old Sal, traveling with her grandparents from Ohio to Idaho in search of her missing mother, entertains them with the story of her friend Phoebe whose mother also left, unwittingly revealing the truth about her own relationship with her mom.
"First Harper Trophy edition, 1996"--T.p. verso.
"Joanna Cotler Books."
Elem. School Library Collection
Wilson's Children
Wilson's Junior High School
Book Links (A.L.A.), July 2000
Keywords: Death -- Fiction; Family life -- Fiction; Friendship -- Fiction; Grandparents -- Fiction; Death -- Fiction; Family life -- Fiction; Friendship -- Fiction; Grandparents -- Fiction